AL-TURAIF DISTRICT OF AL-DIR’IYAH, SAUDI ARABIA: WORLD HERITAGE SITE FACING PERIODIC EXTREME WEATHER EVENTS - Jerome, Pamela; Yosof al-Aidaroos, Mohammad; Hurd, John (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Al-Turaif district of al-Dir’iyah in the Kingdom of Saudi Arabia on the outskirts of Riyadh was inscribed on the World Heritage List in 2010. Al-Turaif site covers approximately 29 hectares with a buffer zone of 238. Nominated under criteria iv, v and vi, the site is an outstanding example of a Najdi settlement, a signiicant human settlement in a desert environment intimately linked to the adjacent Wadi Hanifah (a dry riverbed), site of the irst two Saud States, and connected to the teaching of the Islamic reformer who lived there, Sheikh Mohammad Bin Abdul Wahab. Dating to the 15th century, the site was deliberately destroyed in 1819 by the Ottomans. As such its current state is that of a mud-brick ruin, extraordinarily evocative both for its size and detail, but also for the beauty of its setting within the Arabian plateau landscape. Located at the crest of the escarpment, the area receives very little annual rainfall. However, when there is precipitation, it typically arrives as violent rain events. There are also periodic sandstorms that “sand-blast” the structures. The site is extremely vulnerable to both of these phenomena, because of the steepness of the topography, the ephemeral nature of the construction material that requires cyclic renewal, and the incompleteness of the architecture, no longer being roofed or having the capacity to shed water. This paper will describe the signiicance of the site, its physical nature, and the risks to its survival. It will propose environmental monitoring together with conservation measures that will improve risk preparedness and disaster response. Most of the conservation methods are speciic to mud-brick ruins, but the paper will also include the proposed mobilization of civil society as a tool for use in risk preparedness and disaster response that is applicable to heritage sites in general.